The built environment of schools: Access to unhealthy food outlets and outdoor recreational facilities. (April 2019) - Yang, Meng; Wang, Haoluan; Qiu, Feng
Abstract: This study uses the network-based coverage method to assess the built environment of schools, which includes both unhealthy food outlets and outdoor recreational facilities. Poisson regression models are further adopted to investigate the association between the built environment and neighborhood characteristics. Public and Catholic schools are separately analyzed to obtain a more detailed perspective of the disparity between the two. Results indicate that schools facing the most unfavorable built environment located in the neighborhoods that have (1) higher rates of aboriginal and senior populations, (2) higher percentages of renters (i.e., non-homeowners), (3) more residents with no educational diploma, and (4) substantially lower median income. Overall, unhealthy food sources are more prevalent near schools that are located in neighborhoods with inferior socio-economic status. Policies and relevant programs are discussed. Highlights: Network-based coverage method is used to assess school built environment. We consider both unhealthy food outlets and outdoor recreational facilities. Public and Catholic schools are separately analyzed. Schools face different built environments with disparate neighborhood socio-economic status.